Monochorionic Twin Pregnancy Complicated by Arrhythmia in One Twin: Longitudinal Hemodynamic Effects of Flecainide Cardioversion Assessed by Fetal Venous Doppler - Einum, Anders; von Brandis, Philip; Leirgul, Elisabeth; Ebbing, Cathrine (Journal of Fetal Medicine, 2023)
A parous woman with a monochorionic twin pregnancy presented at gestational week 25 with an uncommon situation. One twin had developed hydrops, but not due to placental transfusion syndrome. The twin had a supraventricular tachyarrhythmia, a rare and severe complication that untreated would threaten the lives of both twins. We present the longitudinal Doppler ultrasound findings when assessing the hemodynamic effects of the arrhythmia and the transplacental treatment with antiarrhythmic medication (flecainide), and how the arrhythmia and the conversion to normal rhythm influenced umbilical and liver circulation in the fetus.
Keywords: antiarrhythmic drugs; Doppler ultrasound imaging; fetal placental circulation; fetal therapy; maternal fetal exchange; monochorionic twins; tachyarrhythmia